Historical perspectives on green structure development: the examples of Stockholm, Sweden and Xi'an, China. (17th November 2019) - Xiu, Na; Ignatieva, Maria; Konijnendijk van den Bosch, Cecil
ABSTRACT: Green structure has undergone many changes during the process of urban development. This paper compares Stockholm, Sweden, and Xi'an, China, in order to illustrate these changes over time and how they reflect the deeper human–nature relationship. This type of analysis can uncover the cultural identity of different cities and clarify urban forms that are common to other geographical locations. We found well-preserved green structure of different periods in the two cities, indicating similar structural development traditions but using different components. Analysis and comparison of three stages of formation revealed that conflicts between the built environment and green structure are an illustration of human–nature interactions, which change with cultural and societal changes in different areas. We argue that rethinking green structure and invoking deep respect for nature is a starting point for resolving such conflicts and the wider environmental crisis.